Boarding House Provider Information with Multi Attribute Utility Theory (MAUT) Method - Suwitno Suwitno; Niki Djanuar Chandra; Benny Daniawan (bit-Tech, 2023)
The increasing rate of population growth in urban areas to find work or study and the high Basic Credit Interest Rates for Home Ownership Loans, the choice of renting a boarding house can be an alternative for those who do not want to stay in the long term. Implementation of Decision Support System provide choices for information system in order to assist the community in choosing a place to live such as a boarding house. One method of Decision Support System is Multi Attribute Utility Theory (MAUT). MAUT can be interpreted as method of systematic comparison by finding the total weight of a set of values in the criteria to obtain results. MAUT method on a web-based information system, it can help people determine the choice of the desired boarding house. The results from the MAUT method will be used an objective consideration for users. The results of this study were tested by Technology Acceptance Model to measure the acceptance of systems. The calculation of TAM uses questionnaire distributed to 88 respondents and based on t-statistics on the TAM test, Perceived Ease of Use (PEOU) against Attitude Toward Using (ATU) is 2.660, Perceived Usefulness (PU) against ATU is 4.218. Then Behavior Intention to Use (BITU) for Actual System Use (ASU) is 16,122 and PU for BITU is 4,218. Where the indicator to have a positive influence when the value is above 1.9894. Meanwhile, ATU against BITU is only 1.179 which means that it does not have a positive influence.